Prematurity and body composition at 6, 18, and 30 years of age: Pelotas (Brazil) 2004, 1993, and 1982 birth cohorts - Caroline Cardozo Bortolotto; Iná S. Santos; Juliana dos Santos Vaz; Alicia Matijasevich; Aluísio J. D. Barros; Fernando C. Barros; Leonardo Pozza Santos; Tiago Neuenfeld Munhoz (BMC, 2021)
Abstract Background We aimed to investigate the association between preterm birth and body composition at 6, 18, and 30 years of age using data from three population-based birth cohort studies. Methods Gestational age (GA), defined by the date of the last menstrual period (categorized in ≤33, 34-36, and ≥ 37 weeks), was gathered in the first 24-h after delivery for all live births occurring in the city of Pelotas, Brazil, in 2004, 1993 and 1982. Body composition was assessed by air-displacement plethysmography. Outcomes included fat mass (FM, kg), percent FM (%FM), FM index (FMI, kg/m2), fat-free mass (FFM, kg); percent FFM (%FFM), FFM index (FFMI, kg/m2), body mass index (BMI, kg/m2 at 18 years in the 1993 cohort and 30 years in the 1982 cohort), and BMI Z-score (at 6 years in the 2004 cohort). We further explored the association of birth weight for GA with body composition indicators and BMI. Crude and adjusted linear regressions provided beta coefficients with 95% confidence intervals (95%CI). Results A total of 3036, 3027, and 3369 participants, respectively, from the 2004, 1993, and 1982 cohorts were analyzed. At 6 years, preterm boys (born at 34-36 weeks) presented lower adjusted mean of FM (β = − 0.80 kg, − 1.45;-0.16, p = 0.046), %FM (β = − 2.39%, − 3.90;-0.88, p = 0.008), FMI (β = − 0.70 kg/m2, − 1.13;-0.27, p = 0.004) as well as lower FFM (β = − 0.4 kg, − 0.77; − 0.12, p = 0.010) and FFMI (β = − 0.3 kg/m2, − 0.46;-0.10, p < 0.001), and BMI Z-score (β = − 0.69,; − 0.99;-0.40, p < 0.001); but higher %FFM (β = 2.4%, 0.87;-3.90, p = 0.008), when compared to boys born at term (≥37). At 30 years, FM (15.7 kg, 0.25;31.1, p = 0.102) was higher among males born at ≤33 weeks. No association was observed for females from the three cohorts and for 18-year-old males. The association of birth weight for GA with body composition and BMI was not significant in any cohort. At 6 years, SGA boys had lower FFMI than boys AGA. Conclusions Our results suggest that preterm birth is associated with decreased body fat and fat-free mass in childhood but higher fat mass in adulthood. Nevertheless, results were only significant for males. SGA boys also showed lower FFMI.